Pengaturan Perlindungan Hukum Atas Publikasi Data Pribadi Anak Korban Kekerasan Seksual Ditinjau Dari Prinsip Kepentingan Terbaik Bagi Anak - Septya Hasna Rahmasari; Syarif Nurhidayat (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The development of technology and the ease of obtaining information, spurred the level of curiosity of the community in exploring cases of sexual violence that occurred in children. These activities are actually not intended for negative things, but rather to channel sympathy and educate the level of vigilance of others. However, sympathy for the coercion of sexual activity has encouraged other parties to unknowingly publish excessive personal data of child victims, so that legal protection is needed that is oriented towards the best interests of the child. So, this research conducts a study related to the legal protection arrangements for the publication of personal data of child victims of sexual violence in terms of the principle of the best interests of the child. The research method used is normative legal research. The approach in this research is a conceptual approach to legislation (statute approach). Data collection techniques are carried out through library research. Analysis technique used is descriptive qualitative. In this study, the conclusions are obtained, first, arrangements related to legal protection of the publication of personal data of child victims of sexual violence have been regulated and found in 5 regulations. Second, based on a review of the principle of the best interests of the child which is derived in several indicators, these provisions are considered to have fulfilled but normatively still need to be strengthened in the form of new norms that are more specific to follow up on cases of publication of personal data of child victims of sexual violence.